Albinism in Tanzania: A Ritual Politics of Silence, Fear, and Subservience - Francis Semwaza (Religions)
Violence against people with albinism (PWAs) in Tanzania continues nearly two decades after mass media reported the first incidents in the mid-2000s. The violence is linked to organ trafficking for use in “magical rituals” that allegedly help politicians and businesspeople to succeed in their endeavors. Over time, as societal awareness grows, the attacks become increasingly clandestine and complex. PWAs themselves, the public, and gray literature frequently relate the violence to the increased political and economic activity and participation following Tanzania’s adoption of political and economic liberalization. However, scholarly research is either silent or mentions the occult practices only in passing. This paper, therefore, explores Tanzania’s institutional arrangements both driving the violence and crippling the efforts at promoting the rights and welfare of PWAs in the wake of increasing political and economic participation in the country. It discusses the ways in which violence against PWAs has evolved alongside political and economic dynamics from the time such incidents came to public attention until the present. I argue that the current approach, whereby advocacy about the rights of PWAs relies on appeasing the state, appears to perpetuate the very beliefs and practices driving the violence. The exploration makes use of first-hand experience through my participation in numerous formal and informal interactions with PWAs, internal and external meetings within the Tanzania Albinism Society (TAS), interviews, and gray literature on the subject.